2013
DOI: 10.1166/jbn.2013.1553
|View full text |Cite
|
Sign up to set email alerts
|

Release of Antimicrobial Peptides from Electrospun Nanofibres as a Drug Delivery System

Abstract: Electrospinning is a very versatile technique, which holds great potentials for several clinical applications. The ability to produce biocompatible nanofibres mimicking the extracellular matrix of the body in combination with both the large surface area and the adsorption/release properties of nanofibres makes drug loaded electrospun fibres very promising for both drug delivery and tissue engineering purposes. An interesting type of molecules to incorporate into electrospun nanofibres are antimicrobial peptide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 0 publications
0
26
0
Order By: Relevance
“…With familiar nano‐silver based products as creams and wound dressings for treating the burns and other infection diseases, development of antimicrobial suture either through coating or loading into fibers can foster its application for wound closure . Advancement of suture fabrication with antimicrobial nanofibers into filaments of suture at the same time retaining its mechanical strength and properties can decrease the need for antimicrobial coating into sutures . Novel approach through combination of antimicrobial agents and/or nanostructured surface with distinctive material geometries to overcome the bacterial adherence and biofilm formation can be effective to reduce the infection rate on wound closure.…”
Section: Recent and Emerging Trendsmentioning
confidence: 99%
“…With familiar nano‐silver based products as creams and wound dressings for treating the burns and other infection diseases, development of antimicrobial suture either through coating or loading into fibers can foster its application for wound closure . Advancement of suture fabrication with antimicrobial nanofibers into filaments of suture at the same time retaining its mechanical strength and properties can decrease the need for antimicrobial coating into sutures . Novel approach through combination of antimicrobial agents and/or nanostructured surface with distinctive material geometries to overcome the bacterial adherence and biofilm formation can be effective to reduce the infection rate on wound closure.…”
Section: Recent and Emerging Trendsmentioning
confidence: 99%
“…Sebe et al [85] reported that the antimicrobial activity of colistin sulfate was improved by 5–6 fold against Acinetobactor baumannii and S. aureus after incorporation into PVA nanofibers. On the other hand, Eriksen et al [86] incorporated several different synthetic AMPs into poly ɛ-caprolactone (PCL) nanofibers and found that only tetracycline hydrochloride retained its activity. A parallel study by Heunis et al [87] also demonstrated that antimicrobial activity of plantaricin 423 decreased from 51,200 to 25,600 arbitrary units mL −1 after electrospinning into PEO nanofibers.…”
Section: Antimicrobial Nanofibers Of Biological Originmentioning
confidence: 99%
“…When considering antimicrobial nanofibers, it is important to consider that evidence supporting the high biocidal efficiency of a novel antimicrobial agent cannot automatically be extrapolated to predict their efficacy after their immobilization onto nanofibers. This is illustrated by the reports on reduced biocidal efficiency of AMPs after incorporation into nanofibers [80,86]. Hence, for applications involving medical implants, an extensive in vivo evaluation of the durability and stability of these nanofibers-based antimicrobial surfaces is needed.…”
Section: Future Prospectsmentioning
confidence: 99%
“…24 However, some AMPs have also been employed in electrospun nanofiber mats. 13,[25][26][27][28][29][30] Electrospinning is a promising tool for peptide nanofiber production. 31 This process allows nanofiber fabrication of diverse materials with diameters ranging from nanometers to micrometers, with high porosity, a large surface area 17,32 and efficient controlled drug release.…”
Section: Introductionmentioning
confidence: 99%
“…After 2 h, the release of the encapsulated molecule was 50%. 25 The cumulative release of plantaricin 423 from electrospun blends of poly(D,Llactide) and poly(ethylene oxide) was evaluated by Heunis and colleagues 26 and exhibited a high initial burst release and a more continuous release of bacteriocin over an 8-day period.…”
mentioning
confidence: 99%